The growth of the mastoid volume in children with a cochlear implant - Tirkkonen Minna; Iso-Mustajärvi Matti; Dhanasingh Anandhan; Linder Pia; Myller Katariina; Dietz Aarno (Nature Research, 2025)
The aim of this study was to understand the mastoid volume development in children who undergo cochlear implantation surgery. Cochlear implant (CI) database of our clinic (Kuopio University Hospital) was reviewed for computed tomography (CT) images of CI patients (age under 12 years at the time of implantation) with a minimum time interval of twelve months between their pre- and postoperative CT. Eight patients (nine ears) were found eligible for inclusion. Three linear measurements were taken by using picture archiving and communication systems (PACS) software and the volume of the MACS was measured with Seg 3D software. The mastoid volume increased on average 817.5 mm3 between the pre- and the postoperative imaging time point. The linear distances measured between anatomical points like the round window (RW)- bony ear canal (BEC), the RW-sigmoid sinus (SS), the BEC-SS, and the mastoid tip (MT)-superior semicircular canal (SSC) increased signifcantly with the age of the patient at both the pre-op and post-op time points. The linear measurements between key anatomical points and mastoid volume showed a positive linear correlation. The correlation between linear measurement and volume were signifcant between the MT-SSC (r = 0.706, p = 0.002), RW-SS (r = 0.646, p = 0.005) and RW-BEC (r = 0.646, p = 0.005). Based on our fndings from the CI implanted patients and comparing it with the previous literature fndings from non-CI implanted patients, we could say that the CI surgery seem to have no efect on the development of mastoid volume in children.